Determination of Factors that may Lead to Acquisition and Transmission of New SARS-CoV-2 Variant VUI-202012/01 in Pakistan- A Multicenter Cross-Sectional Survey - Shafquat, Yusra (International Journal of Pathology, 2021)
Introduction: COVID-19 has become a major public threat. Implementation of no strict preventive measures would increase the cases unless the local community has knowledge of disease and its preventive measures. Emergence of variants and mutant strains is expected with the introduction of mass vaccination and validated treatment, hence making preparedness against them is essential. In this study we have determined the attitude of local population to COVID-19 and its prevention, and the factors associated with compliance with preventive measures. The data will help in estimating the expected increase in disease burden and measures that need to be taken to stop the spread of new SARS-CoV-2 variant VUI-202012/01. Methodology: This cross-sectional survey was performed by the Department of Pathology, Bilawal Medical college for boys and Liaquat University of Medical and Health sciences and included residents of Hyderabad, Jamshoro and Mirpur Khas, from 1st December to 31st December 2020, using a questionnaire on telephone. Knowledge about the disease and the preventive measures were analyzed. Factors associated with compliance with preventive measures were determined using logistic regression. Results: 1020 participants were included. 94.5% frequently washed hands, 89.2% wore masks and 31.6% practiced social distancing. On logistic regression, those with high school education and belonging to occupations of teaching and shopkeepers showed statistically significant association with adherence to precautionary measures. 15.3% participants had taken chloroquine or hydroxychloroquine. Conclusion: Our survey shows most of the participants were not following the recommended preventive measures. Appropriate education of preventive measures and strict reforms are imperative, to stop transmission of new SARS-CoV-2 variant VUI-202012/01.